Encoding of Slowly Fluctuating Concentration Changes by Cockroach Olfactory Receptor Neurons Is Invariant to Air Flow Velocity - Hellwig, Maria; Martzok, Alexander; Tichy, Harald (Frontiers in Physiology, 2019)
The ON and OFF olfactory receptor neurons (ORNs) on the cockroach antenna display a high sensitivity for the rate at which odorant concentration changes. That rate of change acts as a gain control signal that improves the sensitivity of both ORNs for fluctuating concentra-tion changes. By means of extracellular recording techniques, we find in both types of ORNs an increased gain for the rate of concentration change when the duration of the oscillation period increases. During long-period oscillations with slow concentration changes, the high gain for the rate of concentration improves the ORNs ability to detect low rates of concentration changes when the fluctuations are weak. To be useful in plume tracking, gain control must be invariant to the air flow velocity. We describe that raising the level of the flow rate has no effect on the ON-ORN responses to concentration changes down to rates of 2%/s, but exerts a slight increase on the OFF-ORN response during these extremely low rates. At 4%/s, however, the OFF-ORN response is also unaffected by the flow rate level. The asymmetry corresponds with a generally higher sensitivity of the OFF-ORN to concentration changes. Nevertheless, the gain of both ORNs for the concentration rate is robust against the air flow velocity. This makes possible an instantaneous analysis of the concentration rate for both directions of change by one or the other ORN. Therefore, the ON and OFF ORNs are optimized to encode concentration increments and decrements in a turbulent odorant plume.